PENGARUH CORPORATE GOVERNANCE TERHADAP EARNINGS MANAGEMENT (SELAMA DAN SESUDAH KRISIS EKONOMI GLOBAL) - Faris Himadri (Master in Accounting Program, 2013)
This study was aimed to test the influence of managerial ownership, institutional ownership, size of board of commissioners, independent commissioners, and auditor reputation factors on earnings management during global economic crisis and after global economic crisis.The sample was all companies in manufacturing category in Indonesia Stock Exchange (BEI). Observation period was 2007-2008 and 2009-2012 periods. The use of periods was aimed to separate the period during global economic crisis and after global economic crisis or recovery period.The result of this study showed that only independent commissioner variable showed significant negative influence on earnings management, both during global economic crisis and after global economic crisis. Moreover, the result of difference test showed that the influence of corporate governance on earnings management during global economic crisis was relatively similar to the period after global economic crisis.